Produksi dan Komposisi Susu Kambing Peranakan Ettawa Melalui Pemberian Ekstrak Meniran - Puji Astuti; Heru Suripta; NE Sukarini (AGRISAINTIFIKA: Jurnal Ilmu-Ilmu Pertanian, 2017)
This  research  was  conducted  to  determine  the  difference  in  quantity  and quality (specific weight, fat, protein, total solid, total solid non fat, fatty acid omega 6 and 3) of milk in ettawa goat   fed  meniran extract  (Phyllanthus niruri). Experimental  animals  used  in this  study  were  12 peranakan ettawa goat    that  were  producing  at  the  second  lactation  with average  body  weight  of  50  kg  and  milk  production  about  1-2  liters.  They  were divided  into  four  groups,  each  groups  containing  3  animal.  Group  1  (without meniran extract),  group  2  (50 mg meniran extract/kg body weight),   group  3  (100 mg meniran extract/kg body weight), and group  4  (150 mg meniran extract/kg body weight). Quality  of  milk  calculated  at the end  in  research  and  quantity  of  milk  calculated  every  day  twice  a  day  in  the morning and evening. The data obtained in the study were analyzed with ANOVA. The results  showed  there  were  significant  difference  (p<0,05)  in  feed consumption,  milk quantity, but not at   milk quality (specific  weight,  protein,  total  solid  non  fat)  of  Peranakan ettawa goat  fed  meniran extract. Key word : Peranakan ettawa goat, milk quantity dan quality, meniran extract